IMPLEMENTASI KEBIJAKAN PENATAAN, PEMBINAAN DAN PENGAWASAN TOKO MODERN DI KECAMATAN KAJEN KABUPATEN PEKALONGAN - Edi Setiawan; Retno Sunu Astuti (Departemen Administrasi Publik, Universitas Diponegoro, 2018)
Modern Stores in Kajen Subdistrict increase rapidly in terms of numbers. The purpose of this study is to analyze the Implementation of The Modern Store Management, Guidance and Supervision Policy in Kajen Sub District, Pekalongan Regency and to analyze the supporting and inhibiting factors of the Implementation of the Policy. This study uses a qualitative approach, with the analysis of the policy implementatioin of the 5 C Protocol Adil Najam Model. The location of the study in Kajen Sub District. Modern Store policy implementation in Kajen Subdistrict seen from the arrangement (1) has referred to the RTRW Regional Regulation, but there is no legal protection of the Kajen Sub District RDTR and Zoning Arrangement (2) Not all of the Modern Stores construction has IUTM, not all meet the distance requirement and the stores was built at one side of the same road. The Implementation when viewed from the coaching side (1) The OPD coaching executor newly focuses on the Modern Stores Networking, (2) Partnerships with SMEs are not much connected yet, only implemented by Non-Networked Modern Stores. The Implementation when viewed from supervision (1) There is no reporting from the Modern Stores (2) There is no firmness in enforcement of the Perda. The supporting factors of the implementation of the policy are (1) the clarity of the implementers of the implementation and the authority, (2) the existence of a legal protection ranging from local regulations, regent regulation, Service standard, SOP, (3) conducive environmental conditions between the Modern Market and the traditional stores, while the inhibitor factors include (1) weak coordination of the policy implementors, (2) limited personnel lacking firmness in law enforcement, (3) no firmness in enforcement of rules, (4) low awareness of Modern Stores in managing Modern Store Business Licenses (IUTM) (5) limited public understanding of policy. The suggestions that I can convey are (1) need more intensive guidance (2) strengthening of SMEs (3) improving coordination (4) need to increase capacity and motivation for implementing policy implementation (5) need further research related to content from the Modern Store Policy